Executive Committee Minutes 2013-04-04 - Academic Senate:::::::::
Agenda approved. Minutes of 3/14 approved. Chair Report. President Report. Questions for the Provost. APC Charge discussion. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. School of Extended and International Education policy referred. Resolution in Support of an SSU Statement on Civility and Tolerance approved for Senate agenda. Governance Porch Time Fall 2013. Question for the Chief Student Affairs Officer. APC Report. EPC Report. FSAC Report. SAC Report. Question for CFA President. Associated Students Report. Senate Agenda approved.